2016
DOI: 10.1037/a0039996
|View full text |Cite
|
Sign up to set email alerts
|

Why contextual preference reversals maximize expected value.

Abstract: Contextual preference reversals occur when a preference for one option over another is reversed by the addition of further options. It has been argued that the occurrence of preference reversals in human behavior shows that people violate the axioms of rational choice and that people are not, therefore, expected value maximizers. In contrast, we demonstrate that if a person is only able to make noisy calculations of expected value and noisy observations of the ordinal relations among option features, then the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 70 publications
5
70
0
Order By: Relevance
“…Some studies suggest that apparently irrational human behavior could be accounted for by heuristic weighting rules for features that integrate feature valences through feedforward 26,37,38 or recurrent 39,40 neural interactions. Interestingly, a recent study reported that a contextdependent feature weighting can increase the robustness of value encoding to neural noise in later processing stages 38,49 , whereas another recent study provided a unified adaptive gain-control model that produces context-dependent behavioral biases 50 . However, to our knowledge, the optimal policy for these more complex models where the value function is computed by combining multiple features, presented sequentially, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that apparently irrational human behavior could be accounted for by heuristic weighting rules for features that integrate feature valences through feedforward 26,37,38 or recurrent 39,40 neural interactions. Interestingly, a recent study reported that a contextdependent feature weighting can increase the robustness of value encoding to neural noise in later processing stages 38,49 , whereas another recent study provided a unified adaptive gain-control model that produces context-dependent behavioral biases 50 . However, to our knowledge, the optimal policy for these more complex models where the value function is computed by combining multiple features, presented sequentially, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an alternative explanation is that preference reversals are rational (Bordley, 1992;Howes et al, 2016;McNamara, Trimmer, & Houston, 2014;Shenoy, & Yu, 2013;Trimmer, 2013). Rather than taking axiomatic violations as evidence that people's cognitive bounds prevent them from achieving normatively correct decisions, we can assume the cognitive bounds and ask what the optimal decision should be given those limitations (Howes, Lewis, & Vera, 2009;Lewis, Howes, & Singh, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We discuss the implications of these results for theories of human choice. In particular, we argue that while contextual preference reversals appear locally irrational in the sense of violating axioms of decision models, they may in fact be globally rational when the decision environment and cognitive constraints are taken into account (Howes, Warren, Farmer, El‐Deredy, & Lewis, ).…”
Section: Introductionmentioning
confidence: 91%
“…Some studies suggest that apparently irrational human behavior could be accounted for by heuristic weighting rules for features, which integrate feature valences through feedforward 42,43,46 or recurrent 12,44,45 neural interactions. Interestingly, a recent study reports that a context-dependent feature weighting can increase the robustness of value encoding to neural noise in later processing stages 43,54 . However, to our knowledge, the optimal policy for these more complex models in which the value function is computed by combining multiple features, presented sequentially, remains unknown.…”
Section: Discussionmentioning
confidence: 99%